The reimbursement of new medical technologies in German inpatient care: What factors explain which hospitals receive innovation payments?. Issue 3 (4th July 2020) - Ex, Patricia; Vogt, Verena; Busse, Reinhard; Henschke, Cornelia
Abstract: Most hospital payment systems based on diagnosis-related groups (DRGs) provide payments for newly approved technologies. In Germany, they are negotiated between individual hospitals and health insurances. The aim of our study is to assess the functioning of temporary reimbursement mechanisms. We used multilevel logistic regression to examine factors at the hospital and state levels that are associated with agreeing innovation payments. Dependent variable was whether or not a hospital had successfully negotiated innovation payments in 2013 ( n = 1532). Using agreement data of the yearly budget negotiations between each German hospital and representatives of the health insurances, the study comprises all German acute hospitals and innovation payments on all diagnoses. In total, 32.9% of the hospitals successfully negotiated innovation payments in 2013. We found that the chance of receiving innovation payments increased if the hospital was located in areas with a high degree of competition and if they were large, had university status and were private for-profit entities. Our study shows an implicit self-controlled selection of hospitals receiving innovation payments. While implicitly encouraging safety of patient care, policy makers should favour a more direct and transparent process of distributing innovation payments in prospective payment systems.